Psychological impact of COVID-19 pandemic on nurses: A qualitative study - Farzana Danial; Irfan Ullah Khattak (Ukrainian Journal of Nephrology and Dialysis, 2021)
Coronavirus disease is a serious infectious disease that spread very rapidly. Coronavirus not only impacts the general population but also a thread for health care providers. Besides, it psychologically impacts health care professionals especially nurses.Objectives. To explore the psychological impact of the COVID-19 pandemic on nurses working in corona isolation units.Methodology. A qualitative study was conducted using a phenomenological study design. Overall, data were collected from 15 nurses working in tertiary care hospitals of district Nowshera. The study was carried from 1st April 2020 to 20th May 2020. Permission was granted from the District Health Officer of District Nowshera. Keeping the spread of the coronavirus in view, data was collected through semi-structured in-depth telephonic interviews. Electronic consent was also granted from all the concerned participants before data collection. Data were analyzed using Colaizzi’s 7-step method.Results. A total of three themes were generated from the data; Stress, social isolation, and Coping and Self-Care Styles. Nurses working in COVID-19 units experience stress due to constant duty change, fatigue, change in duty placement, and work overload. Also, they experience social isolation due to the fear of getting infected and the disease transmission to their family and other population. Coping and self-care styles such as exercise, physical activity, facing the reality and religious beliefs are important for the nurses to maintain their mental health.Conclusions. The outbreak of COVID-19 psychologically impacts the nurses. Besides, the nurses experience stress and social isolation. The nurses also need coping and self-care styles to maintain their mental health. The role of the health department is very important to highlight this issue and provide proper assistance to the nurses.